Analysis of implementation prevention protocols and community compliance with covid-19 event numbers - Atnesia Ajeng; Wahidin Wahidin; Ika Oktaviani (Alma Ata University Press, 2021)
Background: The Covid-19 pandemic has shaken the world community and disturbed all aspects of human life, for this reason our efforts need to be carried out as an effort to prevent and overcome this pandemic so that it will pass quickly. Therefore, it is necessary to implement health and compliance protocols in the community. Objectives: The aim of this research is to determine the implementation of COVID 19 prevention protocols and community compliance with covid-19 events in Public Health CenterMethods: This research was conducted using regression analysis, correlation and factor analysis. The subjects in this research activity are people who need services at the Puskesmas according to the inclusion and exclusion criteria. The object under study is the community's compliance with the Covid-19 prevention protocol implemented in Tangerang City. A sample of 150 people from 6 Puskesmas in the Tangerang City area in October-November 2020. The main instrument is a questionnaire which is carried out through a blended system approach where research is carried out directly and indirectly in the field, raw data is processed with the help of SPSS and AMOS.Results: it can be seen that the implementation of the health protocol in the Public Health Center in the Tangerang city area has been running quite well about 58.7%, but the level of compliance of the people of the city of Tangerang is still relatively low about 59.3%, however the incidence rate of Covid-19 in Public Health Center in the city of Tangerang is relatively low namely 70.7%. Conclusions: With the knowledge of the above, it is hoped that the local government and other stakeholders can find out and make the basis of facts in making decisions for further handling in order to accelerate the completion of the Covid-19 pandemic.